FTA-LAMP based biosensor for a rapid in-field detection of Globodera pallida—the pale potato cyst nematode - Camacho, Maria João; Albuquerque, Débora C.; Inácio, Maria L.; Martins, Verónica C.; Mota, Manuel; Freitas, Paulo P.; de Andrade, Eugénia (Frontiers in Bioengineering and Biotechnology, 2024)
The combination of a sensitive and specific magnetoresistive sensing device with an easy DNA extraction method and a rapid isothermal amplification is presented here targeting the on-site detection of Globodera pallida, a potato endoparasitic nematode.FTA-cards were used for DNA extraction, LAMP was the method developed for DNA amplification and a nanoparticle functionalized magnetic-biosensor was used for the detection. The combinatorial effect of these three emerging technologies has the capacity to detect G. pallida with a detection limit of one juvenile, even when mixed with other related species. The This combined result deliveredsystem is far more interesting than what a single technology can provide. Magnetic biosensors can be combined with any DNA extraction protocol and LAMP forming a new solution to target G. pallida. The probe designed in this study consistently distinguished G. pallida ((∆Vac binding DV/Vac sensor above 1%) from other cyst nematodes ((∆Vac binding DV/Vac sensor below 1%). It was confirmed that DNA either extracted with FTA-cards or Lab extraction Kit was of enough quantity and quality to detect G. pallida whenever present (alone or in mixed samples), ensuring probe specificity and sensitivity. This work provides insights for a new strategy to construct advanced devices for pathogens in-field diagnostics. LAMP runs separately but can be easily integrated into a single device.